Two-Year Evaluation of AKMI (Indonesian Madrasah Competency Assessment) Implementation at Islamic Elementary School (Madrasah Ibtidaiyah) - Amalia Amalia (UIN Raden Mas Said Surakarta, 2023)
The Indonesian Madrasah Competency Assessment/Asesmen Kompetensi Minimum Indonesia (AKMI) is a form of assessment developed in schools under the auspices of the Ministry of Religious Affairs which refers to PISA (Programme for International Student Assessment) and the National Assessment (AN) system. This research aims to examine the improvement in AKMI results for Madrasah Ibtidaiyah/Islamic Elementary School (MI) students in 2021 and 2022. The approach used is quantitative descriptive and analyzed in percentage form at each level of proficiency. The author also conducted a Focus Group Discussion (FGD) in 2022 with several teachers in the AKMI Follow-up Instructor Candidate class. The results showed a shift in higher proficiency levels in all types of literacy: reading literacy, scientific literacy, numeracy literacy, and socio-cultural literacy. The increase in proficiency levels in these four types of literacy is influenced by massive Continuous Professional Development/Pengembangan Kompetensi Keberlanjutan (PKB) carried out through teacher working groups (KKG–MGMP/MGBK), working groups of madrasah heads, Kriteria Kelulusan Minimum/Graduate Minimum Criteria (KKM) and supervisory working groups (Pokjawas). In addition, the increase occurred due to the Technical Guidance/Bimbingan Teknis (BIMTEK) follow-up of AKMI results for MI teachers. Through this activity, BIMTEK participants can increase their knowledge about literacy